The Human Security Implications of Migration on Zimbabwean Migrant Women in South Africa - Mutambara, Victoria; Maheshvari, Naidu (African Human Mobility Review, 2021)
A large number of people enter the South African borders legally and illegally from Zimbabwe in pursuit of secure, better living conditions. Amongst those people are women. This paper argues that most of the women who migrate to South Africa escape from insecurity in Zimbabwe, only to be confronted with other human security challenges in South Africa. The paper presents an overview of the theoretical framework of the human security paradigm, which helps to unpack how the experiences of Zimbabwean migrant women can be labelled as forms of insecurity. Using qualitative data, the paper discusses the possible human insecurity aspects that force the women to leave their home country and the challenges that they encounter in the host country. The findings of the paper indicate that economic insecurity and poverty highly influence the decisions and choices for migration for most of the women. However, the women’s expectations of better lives and human security appear to contradict their social experiences. The migrant women face multiple forms of discrimination and violence that are constructed around their identities as women, non-citizens and black Africans. Cumulatively, most of the women experience gender-based violence and discrimination from South African citizens, foregrounded in xenophobic sentiments. Therefore, this paper reaches the conclusion that migrant women are victims of the compounded trauma of insecurities, as many of them would have encountered human insecurity consequences in their home country.